Study on The Installation of Urea Synthesis Tower Using Hoisting Structure Based On Truss Support (International Journal of Architecture and Urbanism, 2025)
The paper addresses the scientific and technological issues of securing the installation of heavy objects, including urea synthesis towers, on a building with limited erecting area using hoisting structure based on truss support.